Effectiveness of a sleep education program for pediatricians - AY, NADİYE PINAR; BORAN, PERRAN (WILEY, 2017)
Background: The high prevalence of sleep problems in children and long-term consequences point to the need for early effective interventions, but health-care providers have limited training in pediatric sleep medicine. The aims of this study were therefore to assess the effectiveness of a sleep health-care education program and to develop a Turkish acronym for brief sleep history taking for pediatric primary caregivers in the ambulatory setting. Methods: This was a quasi-experimental study. Four centers were randomly selected from eight training and research hospitals as the intervention group. The control group was recruited during training in subjects other than sleep. Education was provided to the intervention group. Knowledge and attitudes were evaluated in the short and long term. Results: The intervention and the control groups consisted of 132 and 78 pediatricians, respectively. The intervention group scored significantly higher both in the short and the long term. The Turkish acronym (UYKU) was reported to be easy to remember and effective in prompting the correct questions to ask about sleep issues. Conclusions: The Turkish acronym would be useful in the primary care setting to increase the frequency of screening of sleep problems in children. Although education significantly improved knowledge on sleep issues in children, the percentage of participants who lacked confidence in the management of sleep problems in children was still very high, even in the intervention group. We suggest that a broader educational program, carried out more than once, would be more beneficial.
Keywords: obstructive sleep apnea; pediatrics; sleep; sleep disorder; sleep education; CONGENITAL HEART-DISEASE; DEVELOPING-COUNTRIES; BIRTH PREVALENCE; SURGERY; CHALLENGE